Rizzoli & Isles. The complete fourth season [videorecording (DVD)] - Tamaro, Janet
Boston's worst bad guys bring out the best in Detective Jane Rizzoli and Medical Examiner Maura Isles, who use their expert skills and instincts to analyze cadavers, nail criminals and crack the case. In Season Four, the pair's personal lives are as complicated as their professional ones. Smart, sophisticated Maura struggles to cope with issues involving her biological family as she learns more about its gangster past. And brash, down-to-earth Jane reconsiders an ongoing long-distance romance when a handsome new boss sets her pulse pounding. Sixteen murderous, memorable episodes put these best friends to the ultimate test as they face life changes and heartbreaking decisions with their signature humor and humanity- all while solving Boston's toughest crimes.